The feminist Shaw : Shaw and contemporary literary theories of feminism - Mishra, Nishtha (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book takes us through the life and works of George Bernard Shaw as a feminist. It critically explores his major plays to showcase how his works discuss ideas, practices, discourses, and ideologies that are considered to be antecedents to the modern feminist movements. While involvement of male feminists in feminist movements prior to the twentieth century were sporadic, isolated, and relatively unconnected, Shaw used the dramatic form of realistic theatre to communicate socialist and feminist ideas to his contemporary audience. The volume sheds light on how Shaw in his plays and prefaces exposes the iniquities suffered by women. His women characters do not conform to the Victorian notions of femininity; voice self-awareness, self-evaluation, and realisation of personal worth; and break free from the typical mythical representation in literature, to pave the way for the future generations of female character. Shaw's women break the stereotypes of Victorian society to voice and follow their dreams and desires without the fear of societal sanction. Through selections from texts such as Back to Methuselah, Pygmalion, Candida, Arms and the Man, St. Joan, Mrs. Warren's Profession, Man and Superman, The Black Girl in her search of God, and The Simpleton of Unexpected Isles, this book highlights how Shaw gave the world ideologies that have since been adapted by the second and third wave feminists. Foregrounding Shaw's critical role in strengthening feminist characters in modern literature, this volume will be of great interest to scholars and researchers of literature and literary criticism, theatre studies, feminism, and gender studies"--
History, philosophy, and influence. George Bernard Shaw, the forgotten feminist : an introduction -- Oppression/re-presentation of literary myths, archetypes and stereotypes -- Decoding life force and recognising "Shavian Superman" -- Ideology. Shavian new woman : redefining femininity -- Shavian women on Marxist feminism -- Platonic sisterhood of ecofeminist interests -- The third wave women questions : the concerns of Black feminism, post-colonial feminism and LGBTQ theory.
Keywords: Shaw, Bernard, -- 1856-1950 -- Criticism and interpretation; Shaw, Bernard, -- 1856-1950 -- Characters; Women in literature; Feminism in literature; SOCIAL SCIENCE / Ethnic Studies / Asian American Studies